KEMIRINGAN LERENG YANG TEPAT UNTUK MENCEGAH KELONGSORAN DI DESA BARENG KECAMATAN SAWAHAN KABUPATEN NGANJUK - Pasya, Salman Alfaridh; Candra, Agata Iwan; Erwanda, Niko Andika; Fathurrohman, Nadi Rheiza; Qalby, Atsfiela Dzulkhan; Rohman Fauzy, Muhammad Rosyid Abdul; Mahendra, Prendy Eliya (Jurnal Riset Rekayasa Sipil, 2024)
Sawahan District is one of 25 sub-districts in Nganjuk Regency, East Java, Indonesia. Sawahan District has quite good agricultural and tourism potential. Recently, landslides have hit several areas in Nganjuk Regency, one of which is Sawahan District. The area has the potential for landslides because it is dominated by hilly areas with steep slopes and high rainfall intensity. The impact of this disaster included road access that was cut off between the village and the sub-district and the main road leading to the Sedudo Waterfall tour. This study aims to identify soil properties, soil consistency, shear angle, and slope safety factor. The method used is the Atterberg limit test, sieve analysis, soil shear strength, and slope stability calculations using the Bishop method. The test results show that the soil is classified as CL with low plasticity and shear angle, in wet soil it produces a shear angle value of 19.74° and an Fs value of 0.20 while in dry conditions it produces a shear angle value of 24.86° and an Fs value of 0.28. Based on the analysis it is suggested that the slope is 50° to achieve Fs 1.09. This research can be used as a basic reference for planning before construction is carried out and provides slope slope design recommendations for slope planning that is safe to prevent landslides.